The Art of ‘Three carvings’(“三雕”) of Ming and Qing Ancient Buildings in Jinxi County, Jiangxi Province: Cultural Memory and Heritage Preservation in the Digitization Process - Tu, Shaorong; Li, Yue (Journal of Ecohumanism, 2024)
Jinxi County of Jiangxi Province has beautiful forest, with pleasant climate and four distinct seasons. Across the county, a remarkable number of ancient buildings from the Ming and Qing dynasties have survived, reflecting the region’s deep historical and cultural heritage.These ancient buildings of Ming and Qing Dynasties are the living fossils of Jiangxi ancient architecture culture, and the memory and inheritance of Jiangxi culture in the past. A qualitative research method was used, through the local ancient buildings, ancient building internal structure, ancient architectural decoration and surrounding environment landscape data collection, interviews with local residents, control ancient history, analyzing the background under the digital process of jinxi county ‘Three carvings’(“三雕”) the necessity of art and cultural heritage protection and the application value of modern society, the exploration of the relationship between cultural memory and cultural tourism development has important theoretical value and practical significance in both academic research and practice.Cultural memory and heritage protection are closely related to the sustainable development of ancient buildings. These two mainstream concepts are integrated with the inheritance and dissemination significance of the ‘Three carvings’(“三雕”) in ancient buildings and ancient buildings. With the concept of cultural memory and the background of digital process, this paper believes that to preserve the traditional skills of ancient architecture, we should fully explore the concept of heritage protection, combine with the government and universities, and use digital technology to promote the sustainability of historical housing and related legislation.